Goal adoption, preference generation and commonsense reasoning in autonomous intelligent agents - Rafique, Umair (2013)
An autonomous intelligent agent situated in an environment needs to know what the preferred states of its environment should be so that it can work towards achieving them. I refer to these preferred states as “preferences” of the agent. The preferences an agent selects to achieve at a given time are called its “goals” while